Career Path and Motivation Are Entry Points for Medical Recorder's Reward System and Performance - Sri Setia Utami; Kemala Rita Wahidi (Journal of Multidisciplinary Academic, 2022)
This study aims to analyse the effect of career path and motivation on the performance of medical recorders and the reward system as an intervening variable at Harapan Kita Heart and Blood Vessel Hospital (RSJPDHK) simultaneously. The research methodology uses a quantitative approach with path analysis method using the Structural Equation Modelling equation. The sampling technique was carried out by saturated sampling (census) as many as 43 respondents based on the total number of Medical Recorders. The career path will have a significantly stronger positive effect on the performance of medical recorders if it is through the reward system mediating variable. The managerial implication of this research is the continuous strengthening of career paths with full responsibility and justice and upholding Medical Recorder's professional values based on the Decree of the President Director Number HK.02.03/XX.6/0336/2018 concerning Guidelines for the Career Paths of Other Healthcare Professionals to increase the remuneration of Medical Recorders. The reward system variable has the strongest relationship to Medical Recorder performance compared to career path variables and motivation variables. There is an influence of the mediating variable / intervening reward system in mediating the relationship between Career Path and Medical Recorder Performance.